유도결합 플라즈마-마그네트론 스퍼터링 방법을 이용한 저온 폴리실리콘 제조 - 유근철(Keun-Cheol Yoo); 박보환(Bo-Hwan Park); 주정훈(Jung-Hoon Joo); 이정중(Jung-Joong Lee) (Biuletyn Uniejowski, 2004)
Polycrystalline silicon thin films were deposited by inductively coupled plasma (ICP) assisted magnetron sputtering using a gas mixture of Ar and $H_2$ on a glass substrate at $250^{°}C$. At constant Ar mass flow rate of 10 sccm, the working pressure was changed between 10mTorr and 70mTorr with changing $H_2$ flow rate. The effects of RF power applied to ICP coil and $Ar/H_2$ gas mixing ratio on the properties of the deposited Si films were investigated. The crystallinity was evaluated by both X-ray diffraction and Raman spectroscopy. From the results of Raman spectroscopy, the crystallinity was improved as hydrogen mixing ratio was increased up to$ Ar/H_2$=10/16 sccm; the maximum crystalline fraction was 74% at this condition. When RF power applied to ICP coil was increased, the crystallinity was also increased around 78%. In order to investigate the surface roughness of the deposited films, Atomic Force Microscopy was used.